Theoretical analysis of lattice energy and morphology of transition metal dichalcogenides - Lu, Yihua (2018)
This work is aim to understand the composition of chemical bonds and explore the mechanism to form different kinds of morphology of TMD nanocluster. We have developed a universal theory and methodology which can well predict the effective charge of a given materials from variant dimensions. The methodology has to be agile which can be extended to all the materials of all the dimensions, including 3D bulks, quasi 2D layer structures and nanoclusters. for the low dimensional materials, the quantum size effect, layer dependent effect and stacking dependent are all typical tasks to verify the robustness of the new theory extended in the low dimensions. The theory also used to understand the materials' properties in both the static property, like geometry shape, edge stability in nanoclusters, and dynamic property, like growth favorite sites in the nanoclusters.